Risk Factors to Growth Retardation in Major Thalassemia - Uda, Riva; Idjradinata, Ponpon S.; Djais, Julistio TB (Majalah Kedokteran Bandung)
The increasing in the life span of patients with major thalassemia should be followed by increased quality of life. There are factors which can affect growth retardation in these patients. The aim of this study was to find out the risk factors for growth retardation in patients with major thalassemia. An analytical study with cross-sectional design was conducted at Pediatric Thalassemia Clinics of Dr.Hasan Sadikin Hospital, Bandung, in June to July 2006. The subjects of this study were patients with major thalassemia. Inclusion criteria’s were age under 14 years old, had no chronic diseases like tuberculosis, cerebral palsy with complete medical records. Risk factors were the timing of diagnosis, initial and dose of deferoxamine, volume of transfused blood, mean pretransfusion hemoglobin level, family income, and age. Antropometric measurement indices were used to assess the growth which expressed in Z score. Growth evaluated based on height/age (H/A) and growth retardation if H/A <-2 SD. Risk factors for growth retardation were analyzed separately using chi-square test and odds ratio (OR) with 95% confidence interval (CI). Then they were analyzed simultaneously with logistic regression method. Subjects consisted of 152 patients with major thalassemia. Seventy three thalassemia patients were stunted. Analysis showed that age (OR: 5.42, 95% CI:2.32–12.65, p <0.001), dosage of deferoxamine (OR: 4.0, 95% CI: 1.29–12.41, p: 0.016), and family income (OR: 2.32, 95% CI: 1.06–5.06, p: 0.036) were risks factors for growth retardation. Conclusion, risk factors for growth retardation in major thalassemia are age, dosage of deferoxamine, and family income. [MKB. 2011;43(1):21–5].Key words: Major thalassemia, risk factors, stuntedFaktor Risiko terhadap Gangguan Tumbuh pada Thalassemia MayorBertambahnya harapan hidup penderita thalassemia, seyogianya diikuti dengan kualitas hidup seperti anak normal. Terdapat berbagai faktor risiko yang mempengaruhi terjadinya gangguan tumbuh pada penderita thalassemia mayor. Tujuan penelitian ini untuk mengetahui berbagai faktor risiko terjadinya gangguan tumbuh pada penderita thalassemia mayor. Penelitian ini merupakan penelitian analitik dengan rancangan cross sectional di Poliklinik Anak thalassemia Dr. Hasan Sadikin, Bandung, pada bulan Juni–Juli 2006. Subjek penelitian ini adalah penderita thalassemia mayor. Kriteria inklusi adalah penderita berusia <14 tahun, tidak mempunyai penyakit kronik seperti tuberkulosis, palsi serebral, dan rekam medis yang lengkap. Faktor risiko adalah usia saat penegakan diagnosis, usia mulai menggunakan desferoksamin, dosis desferoksamin, volume darah yang telah diterima, kadar hemoglobin rata-rata sebelum transfusi, penghasilan keluarga, dan usia penderita. Dengan antropometri akan ditentukan pertumbuhan berdasarkan skor-Z. Pertumbuhan dinilai dari indeks tinggi badan/usia dan penderita yang mengalami gangguan tumbuh bila tinggi badan/usia <-2 SD. Faktor risiko gangguan tumbuh dianalisis menggunakan uji ki kuadrat dan rasio odds (RO) dengan interval kepercayaaan (IK) 95%, selanjutnya dilakukan analisis dengan metode regresi logistik. Subjek terdiri atas 152 penderita thalassemia mayor. Terdapat 73 penderita yang mengalami gangguan tumbuh. Hasil analisis menunjukkan usia penderita (RO 5,42; IK 95%: 2,32–12,65, p <0, 001), dosis desferoksamin (RO 4,0; IK95%:1,29–12,41, p: 0,016), dan penghasilan keluarga (RO 2,32; IK 95%:1,06–5,06, p: 0,036). merupakan faktor risiko terjadinya gangguan tumbuh. Simpulan, faktor risiko terjadinya gangguan tumbuh pada thalassemia mayor adalah usia, dosis desferoksamin, dan penghasilan keluarga. [MKB. 2011;43(1):21–5].Kata kunci: Faktor risiko, gangguan tumbuh, thalassemia mayor DOI: http://dx.doi.org/10.15395/mkb.v43n1.40